Two Undervalued Functions of the Golgi Apparatus: Removal of Excess Ca2+ and Biosynthesis of Farnesol-Like Sesquiterpenoids, Possibly as Ca2+-Pump Agonists and Membrane “Fluidizers–Plasticizers” - De Loof, Arnold; Schoofs, Liliane (Frontiers in Physiology, 2020)
The extensive literature dealing with the Golgi system emphasizes its role in protein secretion and modification, usually without specifying from which evolutionary ancient cell-physiological necessity such secretion originated. Neither does it specify which functional requirements the secreted proteins must meet. From a reinterpretation of some classical and recent data gained mainly, but not exclusively, from (insect) endocrinology, the view emerged that the likely primordial function of the RER-Golgi complex in all eukaryotes was not the secretion of any type of protein, but the removal of toxic excess Ca2+ from the cytoplasm. Such activity requires the concurrent secretion of large amounts of Ca2+ carrying/transporting proteins acting as a micro-conveyor belt system inside the RER-Golgi. Thus (fitness increasing) protein secretion is subordinate to Ca2+-removal. Milk with its high content of protein and Ca2+ (60-90 mM versus 100 nM in unstimulated mammary gland cells), is an extreme example. The SERCA- and SPCA1a Ca2+/Mn2+ transport ATPases are major players in Ca2+ removal through the Golgi. Both are blocked by the sesquiterpenoid thapsigargin. This strengthens the hypothesis (2014) that endogenous farnesol-like sesquiterpenoids (FLS) may act as the long sought for but still unidentified agonist(s) for Ca2+-pumps in both the ER and Golgi. A second putative function also emerges. The fusion of both the incoming and outgoing transport vesicles respectively at the cis- and trans- side of Golgi stacks, with the membrane system requires high flexibility and fast self-closing of the involved membranes. These properties may - possibly partially - be controlled by endogenous hydrophobic membrane “fluidizers” for which FLS are prime candidates. A recent reexamination of unexplained classical data suggests that they are likely synthesized by the Golgi itself. This game-changing hypothesis is endorsed by several arguments and data, some of which date from 1964, that the insect corpus allatum (CA), which is the major production site of farnesol-esters, has active Golgi systems. Thus, in addition to secreting FLS, in particular Juvenile Hormone(s), it also secretes a protein(s) or peptide(s) with thus far unknown function. This paper suggests answers to various open questions in cell physiology and general endocrinology.